PEMBERDAYAAN MASYARAKAT DALAM USAHA PERIKANAN DENGAN PENDEKATAN BERBASIS ASET (ASSET-BASED COMMUNITY DEVELOPMENT) - Slamet Pamujianto; Supartini, Supartini; Astriawati, Ningrum; Handoyo Widyanto; Kusuma, Ade Chandra (Politeknik Ilmu Pelayaran Semarang, 2024)
The development of the fishery business in Sleman Regency is able to contribute to the production of fish consumption and fry in the Special Region of Yogyakarta. The level of fish consumption needs of the Sleman people has increased from year to year, thus providing opportunities for the people of Sleman to cultivate fish, especially freshwater fish. This opportunity was achieved by the Mina Kepis Fisheries group which gradually developed freshwater fish farming, both for nursery and community consumption. Without the encouragement and support of all parties, small businesses tend to be increasingly helpless, so they must be patient and diligent in coaching and mentoring. Developing a Small and Medium Business Cluster (SME) is indeed not an easy thing, because it is a human development that is loaded with different characters and full of personal interests. . The purpose of this community service is to provide assistance regarding community empowerment programs with the main goal of increasing community income and welfare through strengthening Microfinance Institutions (MFIs), developing entrepreneurial culture, mobilizing community participation and other productive economic business activities based on local and sustainable resources. The service method used is through the mentoring method with an Asset-Based Community Development (ABCD) approach. The results of the service show that KPI Mina Kepis has received the support of the community and the government, as evidenced by receiving donations of funds and assistance from Bank Indonesia and assistance and training in fish farming, in collaboration with UGM so that KPI Mina Kepis gradually moves towards independence. The results achieved by KPI Mina Kepis to date have received encouraging achievements and the results of fish sales, both fish consumption and fish seeds, have increased, These results can help members' income and improve their well-being.